Game | World | Architectonics Transdisciplinary Approaches on Structures and Mechanics, Levels and Spaces, Aesthetics and Perception - Bonner, Marc (Heidelberg University Publishing (heiUP), 2021)
In its current digital, pictorial and viral ubiquity, architecture no longer has to be bodily present, but has a mediating role. As a medial hinge it folds different disciplines of media and art onto the realm of the everyday. Here, the idea of architectonics can be understood as the architectural implications of computer games in a broader sense to address the matter of architecture in game worlds as well as the architecture of computer games themselves. This anthology bundles transdisciplinary approaches around the topics of space, architecture, perception of and worldbuilding in computer games and their media-specific properties. The aim is to show how and under which aspects digital game worlds are constituted. The contributions depart from the beaten tracks of media and game studies, focusing on spatial, architectural and world-shaped phenomena within current digital media culture.